2018
DOI: 10.3390/ijerph15112450
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors and Utilization of the Antenatal Care Services during Pregnancy Associated with Low Birth Weight in Rural Nepal: Analyses of the Antenatal Care and Birth Weight Records of the MATRI-SUMAN Trial

Abstract: Low birth weight (LBW) remains a major public health problem in developing countries, including Nepal. This study was undertaken to examine the association between LBW and maternal factors and antenatal care service utilization, in rural Nepal, using data obtained for a capacity-building and text-messaging intervention, designed to enhance maternal and child health service utilization among pregnant women, in rural Nepal (“MATRI-SUMAN”). The study used a clustered randomized controlled design and was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
41
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 54 publications
15
41
1
4
Order By: Relevance
“…Mothers involved in labor work were five times and mothers who were unemployed or housewives were two times more likely to deliver LBW baby than the employed counterpart. is finding aligns with the study conducted in Lithuania, Vientiane, and Nepal [22][23][24] which revealed that mother's employment status is significantly associated with LBW. e role of education and employment on infant birth weight might be due to various interactions among social determinants of health.…”
Section: Discussionsupporting
confidence: 91%
“…Mothers involved in labor work were five times and mothers who were unemployed or housewives were two times more likely to deliver LBW baby than the employed counterpart. is finding aligns with the study conducted in Lithuania, Vientiane, and Nepal [22][23][24] which revealed that mother's employment status is significantly associated with LBW. e role of education and employment on infant birth weight might be due to various interactions among social determinants of health.…”
Section: Discussionsupporting
confidence: 91%
“…The mothers who deliver female babies had higher odds of bearing low birth weight neonate as compared to those who deliver male neonates. This result is in line with the findings in Ghana (44) and Nepal (45). The association could be explained by the pathophysiologic mechanism in the uterus.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, female neonates had higher odds of being low birth weight babies as compared to male neonates. This result is in line with the ndings in Ghana (40) and Nepal (41). The association could be explained by the pathophysiologic mechanism in the uterus.…”
Section: Discussionsupporting
confidence: 91%